2022
DOI: 10.1021/acs.langmuir.2c02571
|View full text |Cite
|
Sign up to set email alerts
|

Surprising Hydrophobic Polymer Surface with a High Content of Hydrophilic Polar Groups

Abstract: The wetting property of a solid surface has been a hotspot for centuries, and many studies suggest that the hydrophobicity is highly related to the polar components. However, the underlying mechanism of polar moieties on the hydrophobicity remains unclear. Here, we tailor the surface polar moieties of epoxy resin (EP) by ozone modification and assess their wetting properties. Our results show that, for the modified EP with more (60.54%) polar moieties, the polar effect on hydrophobicity cannot be empirically o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Highly polarized oxygen atoms that reside in hydrophilic clusters interact with hydrogen atoms in water molecules via dipolar forces, improving wettability. 103…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Highly polarized oxygen atoms that reside in hydrophilic clusters interact with hydrogen atoms in water molecules via dipolar forces, improving wettability. 103…”
Section: Resultsmentioning
confidence: 99%
“…Highly polarized oxygen atoms that reside in hydrophilic clusters interact with hydrogen atoms in water molecules via dipolar forces, improving wettability. 103 Moreover, the oxygen-containing advantages of carbon electrodes increase their adsorption ability for various substances, preventing electrode materials from dissolving into the electrolyte promoting an uninterrupted connection within the two materials throughout long-term cycling, and facilitating high stability. 104 In summary, an optimal electrode material for SCs should exhibit several key attributes, including a substantial surface area, excellent conductivity, fast ion transfer, and effective hydrophilicity.…”
Section: And Table S6 †)mentioning
confidence: 99%
“…In addition, the C 1s spectra were also analyzed by XPS Fitting software to quantitatively study the chemical components of EP and fluorinated EP, and the details are shown in Figure S1 in the Supporting Information. For the pristine EP in Figure S1a, five chemical groups, including C–C/C–H, CC, C–O, CO, and O–CO are used to fit the C 1s spectra. According to the FTIR spectra, for the fluorinated EP, apart from the above-mentioned five groups in pristine EP, three groups, including CF, CF 2 , and CF 3 are used to fit the C 1s spectra at the high energy area, as seen in Figure S1b–d. Then, based on the fitting results, the content of each chemical group is summarized in Figure h (please refer to Section 1 in the Supporting Information for details).…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis and production of fluoropolymer materials have been found to pose significant environmental risks, leading researchers to actively search for fluoro-free hydrophobic materials. Except for the reported fluoropolymer that had been used in electrowetting devices, polydimethylsiloxane (PDMS) 30,31 was also been used as the hydrophobic and dielectric layer in electrowetting devices. 32,33 Yet, the low T g , low mechanical properties, and weak oil resistance restrict the usage of PDMS in electrowetting devices, especially electrowetting displays.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The synthesis and production of fluoropolymer materials have been found to pose significant environmental risks, leading researchers to actively search for fluoro-free hydrophobic materials. Except for the reported fluoropolymer that had been used in electrowetting devices, polydimethylsiloxane (PDMS) , was also been used as the hydrophobic and dielectric layer in electrowetting devices. , Yet, the low T g , low mechanical properties, and weak oil resistance restrict the usage of PDMS in electrowetting devices, especially electrowetting displays. , One of the reasons that PDMS could be used for electrowetting applications was the sufficient hydrophobicity that arises from the methyl groups located at the periphery of the molecular chain . The low dielectric constant of PDMS is around 2.6–2.7 depending on the molecular weight and temperature .…”
Section: Introductionmentioning
confidence: 99%